2008
DOI: 10.1002/asi.20988
|View full text |Cite
|
Sign up to set email alerts
|

Understanding help seeking within the context of searching digital libraries

Abstract: To date, there has been little empirical research investigating the specific types of help-seeking situations that arise when people interact with information in new searching environments such as digital libraries. This article reports the results of a project focusing on the identification of different types of help-seeking situations, along with types of factors that precipitate them among searchers of two different digital libraries. Participants (N = 120) representing the general public in Milwaukee and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Xie and Cool [17] explored helpseeking or problematic situations that arise in searching digital libraries. They identified fifteen types of help-seeking situations that their 120 novice participants encountered.…”
Section: Frustration In Information Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…Xie and Cool [17] explored helpseeking or problematic situations that arise in searching digital libraries. They identified fifteen types of help-seeking situations that their 120 novice participants encountered.…”
Section: Frustration In Information Retrievalmentioning
confidence: 99%
“…However, multi-class prediction may also be useful, using either regression or a multi-class machine learning method. We also focus on general frustration, but predicting types of frustration may also be useful, e.g., predicting the fifteen types of frustration outlined by Xie and Cool [17].…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, user interaction studies involving DLs have been carried out using direct search observation (Xie and Cool 2009;Joo and Xie 2012) and resource usage logs (Wolfram and Xie 2002). click-through data for results assessment (Smith, Brien, and Ashman 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bilal and Kirby [3] reported that about half of the participants of their user study felt frustration when searching. Xie and Cool [10] demonstrated that most of the time users have problems with formulating and refining search queries. Besides good retrieval performance, a successful search requires users to possess certain skills.…”
Section: Introductionmentioning
confidence: 99%